11 Left ventricular end diastolic filling pressure predicted by left atrial strain measured by feature tracking. (18th April 2016) - Foley, JRJ; Garg, P; Musa, TA; Dobson, LE; Swoboda, PP; Fent, GJ; Haaf, P; Plein, S; Greenwood, JP
Abstract : Introduction: Left ventricular end-diastolic filling pressure (LVEDP) is an invasive measure of LV function obtained at cardiac catheterisation (CC) that predicts prognosis and guides therapeutic strategy. Echocardiographic E/E' ratio has been shown to be inaccurate for estimation of LVEDP. Feature-tracking cardiovascular magnetic resonance (FT-CMR) is a novel method for quantification of myocardial deformation and can be used to quantitatively assess left atrial (LA) function. Currently there is no validated MRI parameter that estimates LVEDP. We hypothesised that LA strain correlates to LVEDP. Methods: 14 patients in sinus rhythm, with severe AS underwent a 1.5T CMR protocol (Ingenia, Phillips Healthcare, Best, The Netherlands). LVEDP was recorded at the time of CC by standard techniques. 4 chamber and mid ventricular short axis steady state free procession cine images were obtained: LA endocardial and epicardial borders were traced manually on the end-diastolic slice and strain measurements were calculated using commercially available post-processing software (CVI42, Circle Cardiovascular Imaging, Calgary, Alberta, Canada). Results: Patients were divided into 2 groups: low EDP (13 ± 2.4mmHg) and high EDP (36.1 ± 3.4mmHg) (p < 0.01). Both  groups were evenly matched for baseline demographics (Table 1 ). Peak atrial longitudinal strain (PALS) was significantly different between low EDP and high EDP group (−21.7 ± 8.5 versus −11.1 ± 2.1% p = 0.01) (Figure 1 ). In multivariable analysis of demographics and CMR parameters PALS was the only determinant of LVEDP independent of other factors (Beta −0.93 p = 0.01). There was a moderate negative correlation between increasing invasive LVEDP and PALS (Pearson's correlation coefficient −0.647, p = 0.009). Conclusion: LA function (PALS) as measured by FT-CMR is independently associated with LVEDP and may have a role in predicting LV filling pressures via a routine CMR protocol.